The Feasibility of Gambier Leaf Tea with the Addition of Red Ginger as An Anti-Aging Functional Drink - Fidela Marsha; Linda Rosalina (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2022)
Free radicals can cause various diseases such as cancer, diabetes, cataracts and premature aging. For that the human body needs antioxidants. Antioxidants can be obtained from plant parts, fruits, and vegetables. Gambier leaves contain catechins which are flavonoid compounds that can be useful as antioxidants. Ginger in addition contains Vitamin A, B6, C, and so on which can also be useful as antioxidants. In addition, ginger can also add aroma and taste to drinks. The method is an experiment with quantitative analysis. The purpose is to determine the feasibility of gambir leaf tea with the addition of red ginger as an anti-aging functional drink in terms of antioxidant activity (laboratory test), aroma, color, and taste (organoleptic test), and panelists' preference level test (hedonic test). This type of research is an experimental quantitative analysis. Data collection techniques are observation and documentation. The formulation used was gambier leaf with red ginger 2.5:1 (X1), 2.5:1.5 (X2), and 2.5:2 (X3). The results showed that the best formulation was 2.5:2 (X3). With a distinctive ginger aroma, warm taste, dark brown color, and favored by panelists. With antioxidant activity of 2354,8155 ppm. Thus, gambier leaf tea with the addition of red ginger is suitable for use as an anti-aging functional drink.